Proteomic analysis of imatinib-resistant CML-T1 cells reveals calcium homeostasis as a potential therapeutic target - Toman, O; Kabickova, T; Vit, O; Fiser, R; Polakova, K Machova; Zach, J; Linhartova, J; Vyoral, D; Petrak, J (Oncology reports, 2016)
Chronic myeloid leukemia (CML) therapy has markedly improved patient prognosis after introduction of imatinib mesylate for clinical use. However, a subset of patients develops resistance to imatinib and other tyrosine kinase inhibitors (TKIs), mainly due to point mutations in the region encoding the kinase domain of the fused BCR-ABL oncogene. To identify potential therapeutic targets in imatinib‑resistant CML cells, we derived imatinib-resistant CML-T1 human cell line clone (CML-T1/IR) by prolonged exposure to imatinib in growth media. Mutational analysis revealed that the Y235H mutation in BCR-ABL is probably the main cause of CML-T1/IR resistance to imatinib. To identify alternative therapeutic targets for selective elimination of imatinib-resistant cells, we compared the proteome profiles of CML-T1 and CML-T1/IR cells using 2-DE-MS. We identified eight differentially expressed proteins, with strongly upregulated Na+/H+ exchanger regulatory factor 1 (NHERF1) in the resistant cells, suggesting that this protein may influence cytosolic pH, Ca2+ concentration or signaling pathways such as Wnt in CML-T1/IR cells. We tested several compounds including drugs in clinical use that interfere with the aforementioned processes and tested their relative toxicity to CML-T1 and CML-T1/IR cells. Calcium channel blockers, calcium signaling antagonists and modulators of calcium homeostasis, namely thapsigargin, ionomycin, verapamil, carboxyamidotriazole and immunosuppressive drugs cyclosporine A and tacrolimus (FK-506) were selectively toxic to CML-T1/IR cells. The putative cellular targets of these compounds in CML-T1/IR cells are postulated in this study. We propose that Ca2+ homeostasis can be a potential therapeutic target in CML cells resistant to TKIs. We demonstrate that a proteomic approach may be used to characterize a TKI-resistant population of CML cells enabling future individualized treatment options for patients.
Keywords: Calcium; signální transdukce; proteom; Signal Transduction; Humans; inhibitory proteinkinas; imatinib mesylát; Proteomics; Imatinib Mesylate; vápník; mutace; lidé; chemorezistence; proteomika; Protein Kinase Inhibitors; homeostáza; chronická myeloidní leukemie; bcr-abl fúzní proteiny; Homeostasis; Fusion Proteins, bcr-abl; nádorové buněčné linie; Proteome; Cell Line, Tumor; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Mutation; Drug Resistance, Neoplasm